1973
DOI: 10.1159/000465651
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Precipitation and Radial Diffusion Methods for Assay of Anti-D Immunoglobulin Preparations

Abstract: The measurement of anti-D concentration has been carried out by two immunoprecipitation techniques utilizing sonicated D-antigen-containing stroma suspended in agarose. One method utilizes single radial immunodiffusion; in the other method, anti-D is moved into the agarose by electrophoresis. The results obtained form both immunoprécipitation techniques were compared to those obtained by a standard 125Iantiglobulin method. The coefficient of variation of the difference between the results obtained by immunopré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1976
1976

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The Coombs' indirect test is only semi-quantitative. The electrophoretic precipitation assay by Hughes-Jones and Gardner [4] is sensitive enough for this type of fractions and plasmas, but they reported a large coefficient of variation (±26% for duplicates on dif ferent plates), and the preparation of stromata is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Coombs' indirect test is only semi-quantitative. The electrophoretic precipitation assay by Hughes-Jones and Gardner [4] is sensitive enough for this type of fractions and plasmas, but they reported a large coefficient of variation (±26% for duplicates on dif ferent plates), and the preparation of stromata is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication Hughes-Jones and Gardner [4] have reported that they have incorporated stromata of Rh-positive red cells in agarose and assayed the anti-D imunoglobulin after radial diffusion or electro phoretic precipitation.…”
Section: Introductionmentioning
confidence: 99%